The Historiographic Production in Colombia on the Revolution and Independence in the Last Two Decades (2004-2024) - Ortega, Francisco A. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Colombia had in the last decade two commemorative cycles around independence (1810-2010; 1819- 21-2019-21). The historiographic production on the Independence and the revolution in the country has been deeply renewed. Economic and social history did not have the tools to perceive and explain the importance of the great political and cultural transformations of the period. Currently, a broader approach is being sought. Several new strategies have emerged that have redefined our understanding of the period.
Keywords: historiography; Colombia; independence; bicentennial; political history